2022
DOI: 10.3390/biom12020260
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Occupational Exposure to Carcinogenic Polycyclic Aromatic Hydrocarbons (cPAHs) and Blood Levels of p53 and p21 Proteins

Abstract: Carcinogenic polycyclic aromatic hydrocarbons (cPAHs) are considered the most serious cancer risk. This study was conducted to assess the effect of acute exposure to cPAHs on cancer biomarker proteins p53 and p21 in occupational workers during the hajj season in Makkah. One hundred five participants were recruited, including occupational workers and apparently healthy individuals; air samples were collected using personal sample monitors to identify the subjects’ exposure to cPAHs. Quantitative analyses of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Saleh et al [ 10 ] assessed differences in the PAHs, including B[ a ]P concentrations, in samples of air inhaled by occupationally exposed and nonexposed groups inhabited in Makkah (Saudi Arabia). They detected B[ a ]P in the mean concentration of 0.082 ± 0.032 ng/m 3 in occupationally exposed workers (bus and truck drivers, police officers, etc.…”
Section: Occupational Exposure To Pahs Including B[ a ...mentioning
confidence: 99%
“…Saleh et al [ 10 ] assessed differences in the PAHs, including B[ a ]P concentrations, in samples of air inhaled by occupationally exposed and nonexposed groups inhabited in Makkah (Saudi Arabia). They detected B[ a ]P in the mean concentration of 0.082 ± 0.032 ng/m 3 in occupationally exposed workers (bus and truck drivers, police officers, etc.…”
Section: Occupational Exposure To Pahs Including B[ a ...mentioning
confidence: 99%
“…Another study conducted in Saudi Arabia on professional workers during the Hajj season to appreciate the effect of intense exposure to polycyclic aromatic hydrocarbons on the cancer biomarker proteins p53 and p21 discovered a positive engagement between short-term PAHs exposure and blood concentrations of p53 and p21. 27 In another study, carried out by Yu et al 28 to explore the influence of prolonged exposure to PAHs on cellular processes occurring in mouse lung fibroblasts (mLFCs), this study concluded that long-term exposure to B a A and B a P increased the protein expression levels of p53 and p21. In most cell types examined, p53 is a short-lived nucleoprotein with a half-life of 5-20 minute.…”
Section: Discussionmentioning
confidence: 95%
“…These results agree with results from another study conducted in Makkah within the same period evaluating different types of PAHs such as benzo[a]pyrene, dibenzo[a,l]pyrene, benzo[a]anthracene, dibenzo[a,h]anthracene, benzo[b]fluoranthene, and indeno[1,2,3-c,d]pyrene. These PAHs were measured in contaminated ambient air and ranged from 6.34 to 37.4 ng/m3, and tumor markers levels were measured in blood serum [ 18 ].…”
Section: Discussionmentioning
confidence: 99%